Difficult Department Chair Conversations Ignatian Style - Janet Kupperman 5014750 (Academic Chairpersons Conference Proceedings, 2017)
The session will explore different types of difficult conversations department chairs have and reasons the encounters may be considered difficult, introduce an Ignatian framework for having conversations, and give participants practice having difficult conversations from an Ignatian perspective.
Keywords: Interpersonal communication; academic leadership; conflict management; difficult conversations